Surface immunoglobulin-mediated B-cell activation in the absence of detectable elevations in intracellular ionized calcium: a model for T-cell-independent B-cell activation. - Brunswick, M (1989)
We recently showed that anti-immunoglobulin conjugated to high molecular weight dextran is 1000-fold more mitogenic for B cells than unconjugated anti-immunoglobulin. This system serves as a model for T-cell-independent type 2 antigens such as haptenated Ficoll, dextran, and bacterial polysaccharides, which can also stimulate B-cell proliferation and antibody production at low concentrations. We show here that conjugated anti-immunoglobulin, at concentrations that stimulate significant increases in expression of major histocompatibility complex class II molecules and incorporation of thymidine into DNA, does not induce detectable modulation of surface immunoglobulin. These results indicate that the facilitated T-cell-independent B-cell activation by polysaccharide antigens may result from inability to modulate surface immunoglobulin, possibly resulting in persistent and/or repetitive signaling. Early large increases in Ca2+ and breakdown of inositol phospholipids presently thought to be involved in transduction of the mitogenic signal are not detectable at low concentrations of conjugated anti-immunoglobulin, raising the possibility that these biochemical events may not in fact be central to this signaling pathway.